Modified bar bending method of thoracoscopic nuss procedure on pectus excavatum: a retrospective single-center study - Jichang Han; Yaru Mou; Dongming Wang; Qiongqian Xu; Jian Wang (BMC, 2023)
Abstract Background Pectus excavatum (PE) is the most common disease of chest wall deformity, with an incidence of 1 in 300-400 births. Nuss procedure has proved to be the best surgical treatment method and has been widely used after clinical use for 30 years. We aimed to review the clinical data of pectus excavatum (PE) of thoracoscopic Nuss procedure adopted the Modified bar bending method of the six-point seven-section type, and compare it with the traditional curved bar bending method to explore the clinical application effect. Methods Forty-six cases of clinical data were summarized of children with PE who adopted the treatment of the Modified bar bending method of the six-point seven-section type from January 2019 to December 2021, and 51 cases were compared of PE children who adopted the treatment of traditional curved bar bending method from January 2016 to December 2018, including the data of age, gender, preoperative symptoms, symmetry, Haller index, operation time, bar bending time, intraoperative bleeding, postoperative complications, bar migration, postoperative effect evaluation, etc. Results The Procedure duration (P = 0.008), bar bending time (P < 0.001), and duration of postoperative pain (P < 0.001) were reduced significantly, and the incidence of bar migration after surgery was reduced as well by the modified bar bending method. There was no difference compared with traditional Nuss produce, like the incidence of evaluation of postoperative effects (Excellent, P = 0.93; Good, P = 0.80; Medium, P = 1.00; Poor, P = 1.00), bar migration (P = 1.00), postoperative complications (P = 1.00), Clavien- Dindo classification of surgical complications (I = 0.165; II = 1.00; IIIa = 1.00; IIIb = 1.00; VI = 1.00; V = 1.00), operative safety, and operative validity. Conclusion Modified bar bending method of the six-point seven-section type, which is a kind of surgical method worth applying and popularizing, and the advantages of minimally procedure duration, bar bending time, and duration of postoperative pain, compared with the traditional bar bending method.